2019
DOI: 10.1016/j.jneuroim.2019.576994
|View full text |Cite
|
Sign up to set email alerts
|

Intracerebroventricular administration of lupus serum induces microglia activation and leukocyte adhesion in the cerebromicrovasculature of mice

Abstract: Background: Central nervous system (CNS) involvement is commonly seen in the patients with system lupus erythematosus (SLE). Mechanisms underlying CNS damage in SLE remain largely unknown. Accumulating evidence suggest that activation of microglia in CNS plays an important role in the inflammatory responses in neurological diseases. The aim of this study is to examine the involvement of microglia in the CNS inflammatory responses induced by circulating serum of SLE patients. Methods: We performed intracerebrov… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 74 publications
2
13
0
Order By: Relevance
“…Consistently, we and others found that IgG-induced neuronal cytolysis occurs in pediatric OMS rather than adult OMS [6,7]. Notably, increased microglial activation is not specific to only OMS, since previous literatures have documented that serum IgG from patients with PD [12] or ALS [13] enhances the activation of microglia and the production of NO, and serum IgG from patients with SLE induced behavioral changes are mediated by microglial activation [14][15][16]. Moreover, several autoantibodies found in patients with OMS [40][41][42][43] also exist in other diseases, such as autoantibody against glycine receptor in progressive encephalomyelitis with rigidity and myoclonus [42,44] or autoantibody against glutamic acid decarboxylase in stiff-person syndrome [44].…”
Section: Sera and The Igg Fraction From Children With Oms And Nb Givesupporting
confidence: 87%
See 1 more Smart Citation
“…Consistently, we and others found that IgG-induced neuronal cytolysis occurs in pediatric OMS rather than adult OMS [6,7]. Notably, increased microglial activation is not specific to only OMS, since previous literatures have documented that serum IgG from patients with PD [12] or ALS [13] enhances the activation of microglia and the production of NO, and serum IgG from patients with SLE induced behavioral changes are mediated by microglial activation [14][15][16]. Moreover, several autoantibodies found in patients with OMS [40][41][42][43] also exist in other diseases, such as autoantibody against glycine receptor in progressive encephalomyelitis with rigidity and myoclonus [42,44] or autoantibody against glutamic acid decarboxylase in stiff-person syndrome [44].…”
Section: Sera and The Igg Fraction From Children With Oms And Nb Givesupporting
confidence: 87%
“…Moreover, the expression of microglial marker soluble CD14 and proinflammatory cytokines is enhanced in CSF from patients with pediatric OMS [10,11]. Additionally, serum IgG from patients or autoantibody existed in patients directly enhances microglial activation in PD [12], ALS [13] and SLE [14][15][16], or initially binds with astrocytes or neurons and further indirectly affects microglial activation [38,39]. Autoantibodies are also detectable in serum and CSF of children with OMS [25,26] and may be contained in serum IgG from children with OMS and NB in our study, although we did not identify these autoantibodies and autoantibodies include IgM besides IgG.…”
Section: Sera and The Igg Fraction From Children With Oms And Nb Givementioning
confidence: 99%
“…Moreover, the expression of microglial marker soluble CD14 and proinflammatory cytokines is enhanced in CSF from patients with pediatric OMS [10,11]. Additionally, serum IgG from patients or autoantibody existed in patients directly enhances microglial activation in PD [12], ALS [13] and SLE [14][15][16], or initially binds with astrocytes or neurons and further indirectly affects microglial activation [43,44]. Autoantibodies are also detectable in sera and CSF of children with OMS [25,26] and may be contained in serum IgG from children with OMS and NB in our study, although we did not identify these autoantibodies and autoantibodies include IgM besides IgG.…”
Section: No/sgc/pkg Signaling Contributes To Conditioned Media-inducementioning
confidence: 99%
“…Notably, increased microglial activation is not specific to only OMS, since previous literatures have documented that serum IgG from patients with PD [12] or ALS [13] enhances the activation of microglia and the production of NO, and serum IgG from patients with SLE induced behavioral changes are mediated by microglial activation [14][15][16]. Moreover, several autoantibodies found in patients with OMS [45][46][47][48] also exist in other diseases, such as autoantibody against glycine receptor in progressive encephalomyelitis with rigidity and myoclonus [47,49] or autoantibody against glutamic acid decarboxylase in stiff-person syndrome [49].…”
Section: The Activation Of Cerebral Cortical and Cerebellar Microgliamentioning
confidence: 99%
See 1 more Smart Citation